STUDENTSâ€™ PROBLEMS IN UNDERSTANDING â€œLANGUAGE ASSESSMENT AND EVALUATION MATERIALSâ€ - Ivan Achmad N; Zunus Indrawan (Teaching English and Language Learning English Journal, 2021)
The aim of this study was to know the Students' Problems in Understanding "Language Assessment and Evaluation Material. The result of this research, the students in 8th semester had problems in understanding materials: 1). the problems in understanding reliability by using Cronbach Alpha materials, 2). the problems in understanding the Normal Curve and Conversion of the Score materials, and 3). the problems in understanding reliability by using (Kuder – Richardson Formula 20 and 21) KR – 20 and 21 materials. I hope that the researcher expected to help students later to be more active in learning language assessment and evaluation of material subjects. For the further researcher, especially English students who are going to conduct the research with the new title, like “student's efforts. Key word: Problems in understanding materials.